Prinsip Kesantunan dalam Kolom Komentar Instagram @nikitamirzanimawardi_172 Kajian Pragmatik - Herawati, herawati; Fadli, Irwan (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2025)
This study aims to examine the form of compliance with the principle of politeness in the speech of social media users in the Instagram comment column @nikitamirzanimawardi_172 based on Geoffrey Neil Leech's pragmatic study. This study uses a descriptive qualitative approach. Data were obtained through direct observation of social media user comments that appeared in several selected posts. The study was conducted based on Leech's theory of politeness principles, with an emphasis on the extent to which social media users adhere to these principles. Based on the analysis that has been done, the data found based on the principle of politeness of language are: The maxim of modesty/humility (0 data), the maxim of agreement (7 data), the maxim of sympathy (9 data), the maxim of wisdom (2 data), the maxim of generosity (4 data), and the maxim of appreciation/praise (13 data). The total data in this study is 35 data. The most dominant data in this study is the principle of praise (approbation maxim). The results of the study show that amidst the dominance of negative comments, there is still an awareness of polite language among some social media users. This reflects an effort to maintain communication ethics in online interactions, even in controversial contexts. Keywords: principles of politeness, Nikita Mirzani, social media, and pragmatics.